Harmful Algal Blooms and Public Health - Grattan, Lynn M. (Harmful Algae, 2016)
The five most commonly recognized Harmful Algal Bloom related illnesses include Ciguatera poisoning, Paralytic Shellfish poisoning, Neurotoxin Shellfish poisoning, Diarrheic Shellfish Poisoning and Amnesic Shellfish poisoning. Although they are each the product of different toxins, toxin assemblages or HAB precursors these clinical syndromes have much in common. Exposure occurs through the consumption of fish or shellfish; routine clinical tests are not available for diagnosis; there is no known antidote for exposure; and the risk of these illnesses can negatively impact local fishing and tourism industries. Thus, illness prevention is of paramount importance to minimize human and public health risks. To accomplish this, close communication and collaboration is needed among HAB scientists, public health researchers and local, state and tribal health departments at academic, community outreach, and policy levels.